Smoking restrictions’ impact on fundamental rights: case of Latvia - Svilāne, Sintija (Riga Graduate School of Law, 2018)
This research is about smoking restrictions in the context of constitutional law, specifically in relation to restriction of fundamental rights. The purpose of the thesis is to determine whether a provision that prohibits smoking inside private passenger cars is compatible with the Constitution of the Republic of Latvia.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Fundamental rights; Latvia